Reforms in the Collegium System: Less Legal, More Ethical - Kumar, DR. Santosh; Singh, Dr. Rang Nath (Journal of Legal and Cultural Analytics, 2023)
The matter of appointment of judges in the higher judiciary has again become a matter of discussion. Prior to the 99th Constitutional Amendment Act, 2014, under Article 124, the President may after consulting such judges of the Supreme Court and the High Courts of the states, whom the President considers necessary to consult for this purpose, by warrant under his hand and seal, to every judge of the Supreme Court shall appoint. In the case of appointment of a Judge other than the Chief Justice, the Chief Justice of India shall always be consulted. Similarly, according to Article 217, the President, after consultation with the Chief Justice of India, the Governor of that State and in the case of appointment of a judge other than the Chief Justice, the Chief Justice of the High Court, by a warrant under his hand and seal, Every Judge shall be appointed.. In this sequentially in the presented article, an attempt has been made to reveal the intention of the constitution makers in relation to how the appointment process of judges in the higher judiciary should be. Although this article may have a reason to be pro-critic, the truth needs to be disclosed.